The opinion of university students towards the implementation of Teaching and Learning of Sciences and Mathematics in English (PPSMI): a case study at MARA University of Technology (UITM) Seremban 3 / Nora Sakila Md Ruzli and Nurul Aathirah Adnan - Md Ruzli, Nora Sakila; Adnan, Nurul Aathirah (2022)
Teaching and Learning of Science and Mathematics in English (PPSMI) has been implemented in the education system since 2003. This study was focusing on the opinion of university students towards the implementation of Teaching and Learning of Science and Mathematics in English (PPSMI). This study also aimed at the perspective of the university student on the implementation of PPSMI and impact on the implementation of the PPSMI. The study framework has two independent variables which are implementation of PPSMI and impact of PPSMI. The dependent variable of this study is the perspective of university students towards PPSMI. The population of this study is 200 respondents that were involved as a participant in UiTM Seremban 3.